TEACHERS’ STRATEGIES TO DEVELOP COGNITIVE DOMAIN STUDENTS’ AT SMPN 33 SINJAI - Nurfadillah; Rum , Eka Prabawati; Ardiana (English Language Teaching Methodology, 2024)
This study was conducted to determine the purpose of the study, namely to describe Teachers’ strategies to develop students’ cognitive domain SMPN 33 Sinjai. The subjects in this study were two teachers and six students of SMPN 33 Sinjai. The purpose of this study is to find out the English teacher strategies to develop students’ cognitive domains and to find out the students’ responses toward the strategies implemented by teachers in developing cognitive domains. The instruments used to collect data are observation, interviews, and documentation. Data analysis in this study is Analysis (QDA), Data Reduction, and Data Display.The results showed that the English teachers' strategies to develop students’ cognitive domain consisted of two strategies, namely the first is simple repetition, the second is using games to get students interested and the students’ responses toward the strategies implemented by the teacher is developing cognitive domains, namely the student response to the simple repetition strategy and the student response using games to get students interested.